Rethinking Social Epidemiology Towards a Science of Change - O$1 (BCampo, Patricia.s; Dunn, James R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
To date, much of the empirical work in social epidemiology has demonstrated the existence of health inequalities along a number of axes of social differentiation. However, this research, in isolation, will not inform effective solutions to health inequalities. Rethinking Social Epidemiology provides an expanded vision of social epidemiology as a science of change, one that seeks to better address key questions related to both the causes of social inequalities in health (problem-focused research) as well as the implementation of interventions to alleviate conditions of marginalization and poverty (solution-focused research). This book is ideally suited for emerging and practicing social epidemiologists as well as graduate students and health professionals in related disciplines.
Foreword.-1. Introduction. Section I: Foundations.-2 (3z(BExplanation,(3y (BPhilosophy and Theory in Health Inequalities Research: Towards a Critical Realist Approach.-3 Values and Social Epidemiologic Research.-4 Population-based Data and Community Empowerment.-5 Differences That Matter. Section II: Context -- 6 Place-based Stress and Chronic Disease: A Systems View of Environmental Determinants.-7 How Goes The Neighbourhood? Rethinking Neighbourhoods and Health Research in Social Epidemiology.-8 Application of Two Schools of Social Theory to Neighbourhood, Place and Health Research.-9 Locating Politics in Social Epidemiology. Section III: Research Tools in Action.-10 Structural Violence and Structural Vulnerability within the Risk Environment: Theoretical and Methodological Perspectives for a Social Epidemiology of HIV Risk among Injection Drug Users and Sex Workers.-11 Realist Review Methods for Complex Health Problems -- 12 Addressing Health Equities in Social Epidemiology: Learning from Evaluation(s).Section IV: Making a Difference.-13 Knowledge Translation and Social Epidemiology: Taking Power, Politics and Values Seriously.-14 Community-Academic Partnerships and Social Change.-15 Producing More Relevant Evidence: Applying a Social Epidemiology Research Agenda to Public Health Practice.-16 Conclusions. Index.s
Keywords: Medicine; Epidemiology; Social sciences; Biomedicine; Biomedicine general; Epidemiology; Public Health/Gesundheitswesen.; Social Sciences, general